Presurgical Perspective and Postsurgical Evaluation of Tibial Pilon Fractures - Piña-Rivas, Alexandra; Mut-Pons, Raul; Llopis, Eva (Seminars in Musculoskeletal Radiology, 2022)
Tibial pilon fractures represent only a small percentage of all fractures of the lower limb. But they are a feared entity, both for the interpreting radiologist and the treating surgeon and, ultimately, for the patient because they involve the weight-bearing area of the joint and often have associated soft tissue injury. These factors make them technically challenging, with poor clinical and functional results in many patients, even when a perfect joint reduction is achieved. Presurgical evaluation with computed tomography and individualized staged management is critical for the prognosis, a definitive treatment strategy, and the prevention of future complications.
Keywords: fracture; tibial pilon; computed tomography; soft tissues